2016
DOI: 10.4236/ajps.2016.76073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Different Tillage Regimes and Nitrogen Levels on Yield and Yield Components of Maize (<i>Zea mays</i> L.)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
5
6
1
Order By: Relevance
“…In other words, the physiological effectiveness of maize crop to partition the dry matter into its cost effective (grain) yield than generation of whole-plant biomass increased under ZT and RT compared to CT. These results are not in line with the findings of [48] who stated that higher harvest index was observed where conventional tillage was applied compared to minimum tillage.…”
Section: Maize Growth and Yieldcontrasting
confidence: 99%
“…In other words, the physiological effectiveness of maize crop to partition the dry matter into its cost effective (grain) yield than generation of whole-plant biomass increased under ZT and RT compared to CT. These results are not in line with the findings of [48] who stated that higher harvest index was observed where conventional tillage was applied compared to minimum tillage.…”
Section: Maize Growth and Yieldcontrasting
confidence: 99%
“…Maize planted under deep tillage and mulch obtained highest vegetative and root biomass probably because deep tillage resulted into good soil texture whereas, mulch conserved moisture for crops. In support of this results, Shahid et al (2016) reported highest plant biomass of maize under deep tillage. Similarly, Hou et al (2012) recorded an increase in plant biomass of maize under mulch.…”
Section: Resultssupporting
confidence: 78%
“…In recent studies, Shahid et al (2016) reported highest vegetative biomass harvested on maize planted under deep tillage while lowest biomass was recorded from minimum tillage. Memon et al (2013) found that deep tillage yielded high production of biomass in maize, and improved essential nutrients required by livestock.…”
Section: Introductionmentioning
confidence: 99%
“…The operation of rotavator destroyed the weeds that provided more favorable environment for crop plants to efficiently utilize the available soil moisture, nutrients, space and solar radiation. Our results are in line with those of [26,27]. Among weed control methods, significantly highest biological yield was obtained from treatment of hoeing at 15, 30 and 45 DAS followed by the treatment of hoeing at 15 and 30 DAS which was statistically similar with the application of herbicide i.e.…”
Section: Days To Silkingsupporting
confidence: 91%